A miniature seven-hole probe air data system and its application on spin prediction. Issue 3 (September 2016) - Li, Shaoze; Gu, Yunsong; Han, Jiexing; Wang, Qite
A miniature air data system based on a seven-hole probe was developed for real-time, in-flight measurement of wind flow deviation angle and inertial parameters. The system is very small in size and weighs only 150 g, especially suitable for flight tests with miniature unmanned aerial vehicles (UAVs). It is capable of measuring angle of attack (AOA) and angle of sideslip (AOS), ranging up to ±78°. The exposed part is a slender probe fixed on the nose of the aircraft, which is only 4 mm in diameter. A spin flight test was conducted with a delta-wing, slender body unmanned aircraft; experimental results demonstrate the complete spinning process. The synchronized measurement of AOA, AOS and angular rate clearly revealed the different phases of spin entry. Furthermore, a spin prediction criterion based on the sideslip changes at high AOA is given. Flight test results show that the prediction approach based on air data can forecast spin entry earlier than the conventional approach based on angular rate, which makes incipient spin detection possible.